Influence of the CO2 Content in Shielding Gas on the Temperature of the Shielding Gas Nozzle during GMAW Welding - Martin Lohse; Marcus Trautmann; Uwe Füssel; Sascha Rose (Journal of Manufacturing and Materials Processing, 2020)
Gas metal arc welding torches are commonly chosen based on their current-carrying capacity. It is known that the current-carrying capacity of welding torches under CO2 is usually higher than under argon dominated shielding gases. In this publication, the extent to which this can be attributed to the shielding gas dependent arc radiation is investigated. For this purpose, the influence of the shielding gas on the thermal load of the shielding gas nozzle of a GMAW torch was calorimetrically measured. These experiments were carried out for four different shielding gases (argon, CO2, and two argon/CO2 mixtures). The measurements were all performed at an average current of 300 A. The welding current was set by adjusting the wire feed rate or the voltage correction. For each case, a separate set of experiments was done. It is shown that the changed arc radiation resulting from the different shielding gases has an influence on the heat input into the gas nozzle, and thus into the torch. For the same shielding gas, this influence largely correlates with the welding voltage.